Annular leukocytoclastic vasculitis associated with anti-tuberculosis medications: a case report - Kumutnart Chanprapaph (2017)
Introduction: Anti-tuberculosis drug-induced cutaneous leukocytoclastic vasculitis has been rarely reported. To the best of our knowledge, this is the first reported case of annular leukocytoclastic vasculitis associated with anti-tuberculosis drug administration. Case presentation: We report a case of annular leukocytoclastic vasculitis induced by anti-tuberculosis medication. A 62-year-old Thai man presented to our facility with a generalized exanthematous rash on his trunk and extremities that resolved shortly afterwards. Subsequently, he developed multiple, erythematous-to-purplish, non-blanchable macules and papules with an annular arrangement on his extremities. The skin rash occurred after two weeks of anti-tuberculosis medication. The histopathology of the purpuric skin lesion was consistent with leukocytoclastic vasculitis. The skin lesion improved after discontinuation of the anti-tuberculosis drugs and treatment with oral antihistamine and topical corticosteroid drugs. Streptomycin, ethambutol and ofloxacin were administered as second-line anti-tuberculosis therapy during his hospitalization. No adverse reactions were observed. Conclusions: Leukocytoclastic vasculitis should be considered in the differential diagnosis of annular non-blanchable macules and papules. Although rare, anti-tuberculosis drugs should be considered potential causes of drug-induced annular leukocytoclastic vasculitis.